2013
DOI: 10.1080/07294360.2013.777032
|View full text |Cite
|
Sign up to set email alerts
|

A synopsis of the mental health concerns of university students: results of a text-based online survey from one Australian university

Abstract: Within the university community, student demographic data highlights a high level of cultural diversity and an "at-risk population" for the onset of mental health problems. Moreover, the transition to higher education is itself associated with a range of emotional, social and academic demands that can cause psychological distress. Therefore, at any one time a substantial number of students may be attempting to complete university studies while managing problematic symptoms, behaviours, or an emerging, or diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 26 publications
1
56
0
6
Order By: Relevance
“…Australian research suggests that among university student populations more than half are unlikely to seek help for mental health issues (Stallman & Shochet, 2009;Wynaden, Wichmann, & Murray, 2013). Students report not wanting to be seen as less capable than their peers and/or not knowing where to seek help.…”
Section: Help-seekingmentioning
confidence: 99%
“…Australian research suggests that among university student populations more than half are unlikely to seek help for mental health issues (Stallman & Shochet, 2009;Wynaden, Wichmann, & Murray, 2013). Students report not wanting to be seen as less capable than their peers and/or not knowing where to seek help.…”
Section: Help-seekingmentioning
confidence: 99%
“…It was revealed that constancy was the strongest predictor of both environmental mastery and purpose in life. Constancy that reflects determination, personal responsibility, and an uncompromising attitude can make sense as managing the multiple and complex appeals of student life (Scanlon et al, 2010;Wynaden et al, 2013) will likely require deep commitment and persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Grades matter to millennials. Grade-related stress is driving growing rates of depression in college-age students (e.g., Wynaden, Wichmann, & Murray, 2013). As Wilson and Gerber (2008) highlighted, students question the assumption that "admission to college confirms that one is actually equal to the task" (p. 34).…”
Section: Kirstie Mcallummentioning
confidence: 99%